2021
DOI: 10.1177/14782103211025428
|View full text |Cite
|
Sign up to set email alerts
|

‘There was no freedom to leave’: Global South international students in Portugal during the COVID-19 Pandemic

Abstract: This article looks at the impact of the COVID-19 pandemic on international students, focusing on Portuguese-speaking African and Brazilian students during the lockdown of spring 2020. Using evidence from interviews conducted with 27 students domiciled in Portugal, we illustrate some of the challenges faced by students when coping with the pandemic, including difficulties in meeting the cost of tertiary education and the centrality of working to sustain their stays abroad, alongside the emotional impact of prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 54 publications
2
23
0
2
Order By: Relevance
“…In regard to what we know about the collateral effects of this immobility turn from prior studies, during the initial lockdown period of Spring 2020, research looking at the impact of the pandemic on international students in Portugal, including both credit mobility exchanges and more settled student migrants, illustrated the extent of the transformation in international student life during the rapid shutdown of society, including the closure of university facilities, leading to prolonged domestic confinement [1][2][3]23].…”
Section: An Immobility Turn?mentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to what we know about the collateral effects of this immobility turn from prior studies, during the initial lockdown period of Spring 2020, research looking at the impact of the pandemic on international students in Portugal, including both credit mobility exchanges and more settled student migrants, illustrated the extent of the transformation in international student life during the rapid shutdown of society, including the closure of university facilities, leading to prolonged domestic confinement [1][2][3]23].…”
Section: An Immobility Turn?mentioning
confidence: 99%
“…While the impact of the pandemic on international students has been considerable, as we have explored in prior publications, much of what has taken place in their lives is self-evident and, hopefully, temporary, meaning that their transitions are likely to be delayed rather than curtailed [1][2][3]. While this may be due in part to students' resilience, we might also want to consider the role played by higher education institutions, which have faced practical difficulties in hosting students during the pandemic, many of whom have enhanced support needs.…”
Section: Introductionmentioning
confidence: 99%
“…The retention of existing international students, and attraction of new students will be paramount for the future sustainability of global academic institutions. Further, research has identified a need to explore the concerns and experiences of international students during the COVID-19 outbreak [3,21,22]. According to the Student Covid Insights Survey (SCIS) conducted by the Office for National Statistics (ONS) in 2020, the COVID-19 pandemic has affected the mental health and well-being of over 50% of students in higher education in England [23].…”
Section: Introductionmentioning
confidence: 99%
“…Such findings suggest that international students from these regions may experience additional financial hardships and additional challenges in the adaptation to online teaching and learning. In Portugal, for instance, African and Brazilian students have faced a complex set of challenges, from economic hardships, emotional distress and adaptation to online teaching ( Malet Calvo et al, 2021 ).…”
Section: Mitigating the Effect Of Covid-19 On International Studentsmentioning
confidence: 99%